PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP KEMAMPUAN KOMUNIKASI SISWA PADA MATA PELAJARAN IPS KELAS V SEKOLAH DASAR - Hazhari, Alvan; Pamungkas, Maya Sih Hika (Journal of Professional Elementary Education, 2024)
This study aims to determine the effect of the jigsaw learning model on students' communication skills in the social studies subject for Class V SD Negeri Citerep, Walantaka District, Serang City. This research is a quantitative survey method. The research sample consisted of 28 students. The instrument used was a closed questionnaire to measure student responses to the jigsaw learning model and students' communication skills. The data analysis technique used is correlation analysis and regression analysis. The results of the correlation analysis obtained a correlation coefficient of 0.83. The results of regression analysis obtained a value of 55.66 and at a significant level of 5% or 0.05 it was 4.22. Because then H0 rejected, with a correlation coefficient of 0.83, it can be concluded that there is a significant effect of the jigsaw learning model on students' communication skills in the social studies subject of Class V SD Negeri Citerep, Walantaka District, Serang City of 68.89%